MITOS REBO WEKASAN DALAM PERSPEKTIF PSIKOLOGI AGAMA ISLAM - Rizal Arifqi (Al Ghazali, 2022)
Abstract Traditional ceremonies are an integral part of the society that preserves them, for people traditional ceremonies are sacred things that have magical elements. Traditional ceremonies carried out by the community are not just routine activities, but have deep and important meanings. This research was conducted using a field study type of research, where the researcher went directly to the place where the tradition was carried out, so that what was written by the researcher actually became a reality in the area. Myth is a form of primordial intellectual expression of various religious attitudes and beliefs. Meanwhile, Rebo Wekasan is a phenomenon that occurs in society due to the intensive acculturation of Javanese culture with Islam. Keywords: Myth, Rebo Wekasan, Psychology